Immunotherapy for TB. (June 2012) - Doherty, T Mark
Mycobacterium tuberculosis was one of the first human pathogens to be identified as the cause of a specific disease – TB. TB was also one of the first specific diseases for which immunotherapy was attempted. In more than a century since, multiple different immunotherapies have been attempted, alongside vaccination and antibiotic treatment, with varying degrees of success. Despite this, TB remains a major worldwide health problem that causes nearly 2 million deaths annually and has infected an estimated 2 billion people. A major reason for this is that M. tuberculosis is an ancient human pathogen that has evolved complex strategies for persistence in the human host. It has thus been long understood that, to effectively control TB, we will need to address the ability of the pathogen to establish a persistent, latent infection in most infected individuals. This review discusses what is presently known about the interaction of M. tuberculosis with the immune system, and how this knowledge has been used to design immunotherapeutic strategies.